Overcoming the Persistence of Inequality and Poverty - FitzGerald, Valpy; Heyer, Judith; Thorp, R.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
International experts evaluate new policy directions in economic development and poverty reduction, building on the ideas of a pioneer in the new discipline of Development Studies, Frances Stewart. Combing ideas and evidence on technological change, human development and conflict prevention to address the issue of the persistence of inequality.
Keywords: Economic policy; Public policy; Political sociology; Political economy; Political science; Social structure; Social inequality; Development Policy; Public Policy; Political Sociology; International Political Economy; Political Science; Social Structure, Social Inequality